2011
DOI: 10.1200/jco.2010.28.4521
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Transplantation Risk Factors for Delirium Onset and Severity in Patients Undergoing Hematopoietic Stem-Cell Transplantation

Abstract: A B S T R A C T PurposeTo determine pre-and post-transplantation risk factors for delirium onset and severity during the acute phase of myeloablative hematopoietic stem-cell transplantation (HSCT). Patients and MethodsNinety adult patients with malignancies admitted to the Fred Hutchinson Cancer Research Center for their first HSCT were assessed prospectively from 1 week before transplantation to 30 days after transplantation. Delirium was assessed three times per week using the Delirium Rating Scale and the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
(21 reference statements)
2
37
1
1
Order By: Relevance
“…These cytoprotective effects of APC were dependent on the presence of protease activated receptor (PAR)1, a receptor expressed by multiple cell types that can be activated by various proteases including APC. This previous study 5 taken together with the current work 4 suggests that low thrombin levels can protect against diabetic nephropathy by more than one mechanism. First, thrombin may cause enhanced APC generation after binding to thrombomodulin, resulting in PAR1-dependent cytoprotective effects on endothelium and inhibition of apoptosis of renal endothelial cells and podocytes.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…These cytoprotective effects of APC were dependent on the presence of protease activated receptor (PAR)1, a receptor expressed by multiple cell types that can be activated by various proteases including APC. This previous study 5 taken together with the current work 4 suggests that low thrombin levels can protect against diabetic nephropathy by more than one mechanism. First, thrombin may cause enhanced APC generation after binding to thrombomodulin, resulting in PAR1-dependent cytoprotective effects on endothelium and inhibition of apoptosis of renal endothelial cells and podocytes.…”
supporting
confidence: 57%
“…5 In addition, delirium and neurocognitive function can be objectively measured using well-validated instruments, highlighting the utility of these outcomes in future studies of CNS disease associated with HHV-6. The study by Zerr et al also identifies more advanced underlying disease as a risk for an episode of delirium associated with HHV-6 and confirms previously reported variables associated with HHV-6 reactivation after HCT: cord blood or unrelated cell source.…”
Section: Org Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Delirium is particularly prevalent in advanced disease. Two recent studies of delirium in hematopoietic cell transplantation found that specific factors, including higher pretreatment alkaline phosphatase and blood urea nitrogen levels and poorer executive function, were associated with increased onset or severity of delirium in the acute phase of transplant [41]. Post-transplant, reactivation of human herpesvirus-6 in the bloodstream, higher doses of opioid medications, increased pain, and higher blood urea nitrogen were also associated with onset or severity of delirium [41,42].…”
Section: Cognitive Impairmentsmentioning
confidence: 96%
“…17 Re-analysis of the same 90 patient HSCT sample in 2011, focused on post-transplant risk factors and concluded that the only pre-transplant risk factors were higher mean alkaline phosphatase and blood urea nitrogen levels, while the only post-transplant risk factor for delirium onset was higher doses of opioid medications. 18 Beglinger et.al, reported that pre-transplant risk factors for delirium in HSCT patients included decreased white blood cell count, hemoglobin, and platelet count. 6 …”
Section: Introductionmentioning
confidence: 99%